(untitled) (Journal of Enam Medical College, 2014)
Background: Chronic obstructive pulmonary disease (COPD) is usually associated with polycythemia. It is assumed that systemic inflammatory components of COPD can interfere with erythropoietin and can result in anemia of chronic disease which will impair the functional capacity of these patients and also increase morbidity and mortality. Objective: To evaluate anemia status in COPD patients. Materials and Methods: This cross-sectional study was conducted in clinically stable 50 COPD patients in the outpatient department of Medicine in Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during the period of July to December 2011. The demographic characteristics, smoking habit, duration of disease, types and severity of anemia, BMI and results of 6-minute walk test were recorded. Results: Out of 50 COPD patients, 76% were male and 24% were female. Among them 32% patients were anemic, 20% were polycythemic and 48% patients had normal hemoglobin. Among the anemic patients with COPD, 87% were male and 13% were female,75% were mildly anemic and 4% moderately anemic, 62.5% had normocytic and 37.5% had microcytic anemia. Conclusion: Anemia in COPD patients is often overlooked and underestimated. Clinicians should be aware of the presence of anemia in patients with COPD so that appropriate treatment could be initiated to improve the quality of life and prognosis DOI: http://dx.doi.org/10.3329/jemc.v4i3.20943 J Enam Med Col 2014; 4(3): 151-155